2008
DOI: 10.1016/j.joca.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in synovial fluid and serum biomarkers with exercise and early osteoarthritis in horses

Abstract: Six synovial fluid and serum biomarkers were useful in separating early experimental OA from exercise alone but synovial fluid CTX1 and serum Col CEQ and CTX1 were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
213
6
19

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(265 citation statements)
references
References 28 publications
27
213
6
19
Order By: Relevance
“…This antibody has previously been shown to recognize the neoepitope in equine tissue (17). Lyophilized tendon (30 mg) was suspended in 0.75 ml of TAPSO buffer (100 mM TAPSO, 10 mM CaCl, pH 8.2) and heated at 90°C for 35 min to denature the collagen.…”
Section: ϫ3mentioning
confidence: 99%
See 1 more Smart Citation
“…This antibody has previously been shown to recognize the neoepitope in equine tissue (17). Lyophilized tendon (30 mg) was suspended in 0.75 ml of TAPSO buffer (100 mM TAPSO, 10 mM CaCl, pH 8.2) and heated at 90°C for 35 min to denature the collagen.…”
Section: ϫ3mentioning
confidence: 99%
“…Matrix age can also be assessed indirectly by measuring markers of collagen degradation. The cross-linked telopeptide of type I collagen (ICTP) (16) and collagenase-generated neoepitope (17) have been used previously as markers of collagen turnover in a variety of tissues.…”
mentioning
confidence: 99%
“…DJD is highly prevalent in humans (Brooks 2002) and in animals, especially in dogs (Biasi et al 2005) and horses (Frisbie et al 2008, Baccarin et al 2012. DJD is also commonly reported in cattle (Persson et al 2007, Heinola et al 2013), but to date, descriptions of DJD in buffaloes and mini cattle have not been found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Frisbie et al (2008) took synovial samples at weekly intervals and found that most of the influence caused by arthrocentesis disappeared after two weeks. On the other hand, taking samples with such frequency could have influenced the data and increased the incidence of iatrogenic (septic) inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration was expressed as pg/ml (substance P), μg/ml (C1,2C), and ng/ml (CS846). All assays had been previously validated for use with equine SF (Frisbie et al, 1999;Celeste et al, 2005;de Grauw et al, 2006;Frisbie et al, 2008;Piat et al, 2012). The intra-and inter-assay coefficients of variation for the evaluation of these SF biomarkers were all < 5% or < 13%, respectively.…”
Section: Biomarker Assaysmentioning
confidence: 99%